2024
DOI: 10.1007/s12015-024-10685-8
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes Derived from Adipose Stem Cells Enhance Angiogenesis in Diabetic Wound Via miR-146a-5p/JAZF1 Axis

Dehui Che,
Xinjian Xiang,
Juan Xie
et al.

Abstract: Chronic trauma in diabetes is a leading cause of disability and mortality. Exosomes show promise in tissue regeneration. This study investigates the role of exosomes derived from adipose stem cells (ADSC-Exos) in angiogenesis. MiRNA-seq analysis revealed significant changes in 47 genes in human umbilical vein endothelial cells (HUVECs) treated with ADSC-Exos, with miR-146a-5p highly expressed. MiR-146a-5p mimics enhanced the pro-angiogenic effects of ADSC-Exos, while inhibitors had the opposite effect. JAZF1 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
0
0
Order By: Relevance
“…Angiogenesis: Che et al found that ADSC-exos upregulated miR-146a-5p in HUVECs, inhibited the expression of the downstream protein JAZF1, promoted the expression of VEGFA, and consequently facilitated angiogenesis in diabetic wounds. 105 Huang et al demonstrated that NFIC in ADSC-exos could promote miR-204-3p transcription to inhibit downstream gene HIPK2 in HUVECs, thus promoting angiogenesis. 104 Wang et al found higher circ-Astn1 expression in ADSCs than in EPCs.…”
Section: Results Sectionmentioning
confidence: 99%
“…Angiogenesis: Che et al found that ADSC-exos upregulated miR-146a-5p in HUVECs, inhibited the expression of the downstream protein JAZF1, promoted the expression of VEGFA, and consequently facilitated angiogenesis in diabetic wounds. 105 Huang et al demonstrated that NFIC in ADSC-exos could promote miR-204-3p transcription to inhibit downstream gene HIPK2 in HUVECs, thus promoting angiogenesis. 104 Wang et al found higher circ-Astn1 expression in ADSCs than in EPCs.…”
Section: Results Sectionmentioning
confidence: 99%